CFD-based irreversibility analysis of avant-garde semi-O/O-shape grooving fashions of solar pond heat trade-off unit. (June 2021) - Liu, Chao; Hashemian, Mehran; Shawabkeh, Ali; Dizaji, Hamed Sadighi; Saleem, S.; Mohideen Batcha, Mohd Faizal; Wae-hayee, Makatar
Abstract: To attain a full-fledged design of a spiral piping system utilized in solar ponds, making a balance between thermal and frictional factors is a critical but difficult task. The present study proposes various designs of spiral piping system (SPS) characterized by the avant-garde arrangement of semi-O/O-shape grooves engraved on the wall of the pipe. In all of the proposed revolutionary grooving designs, the general number of annular grooves was kept at 20. These unorthodox configurations make unique thermal and frictional behavior and subsequently each of them bears distinct irreversibilities. The performance of the proposed configurations was examined based on the caused irreversibilities. Due to the geometrical structure of spiral pipe, the radius of the innermost turn is smaller than that of the outermost turn so selecting each of the ends as an inlet may lead to different results. In order to clarify the impact of inlet position on entropy generation, both inlet positions (the innermost and the outermost) were tested. This is a CFD-based study with experimental validation. The Finite Volume Method (FVM) was used as a discretization method to solve flow-thermal governing equations. The k-omega SST model was employed for modeling turbulence flow inside the GSPS. A high-resolution scheme and fourth order pressure-velocity coupling method were selected to calculate advection terms and the sequential calculation of the involved equations, respectively. To simulate the thermal condition of the lower convective zone (LCZ) of the salinity-gradient solar pond (SGSP) the outer wall of the spiral piping system was subjected to a constant temperature of 360 K. Flow velocity was varied from 0.1 m/s to 0.6 m/s to find its effect on the Nu∗, N E, merit function (MF), heat transfer improvement index (HTI index), S ˙ t h e r m a l, S ˙ f r i c t i o n a l, and η W − S . Generally, HTI index, η W − S, and Nu∗ voted to the competency of the case ''c''. Entering flow from the innermost section preferred to the outermost section since it causes reasonable results in terms of HTI index, η W − S, and MF. Among grooved SPSs, cases ''c'' and ''b'' make the highest and the lowest S ˙ g e n, T h e r m a l, respectively, whereas this is totally inverse for S ˙ g e n, F r i c t i o n a l . The highest values of HTI index for flow velocities of 0.1 m/s and 6 m/s are 1.173 and 1.003 which are related to case ''d'' and case ''c'', respectively. Moreover, almost for all flow rates case ''c'' has the highest η W − S so that for 0.1 m/s and 6 m/s its values are 5% and 1.175%, respectively. Graphical abstract: Image 1 Highlights: Revolutionary grooving fashions were studied based on CFD technique. Each of cases was analyzed based on S g e n ′, N S, Nu∗, N E, HTII index ( N H ), MF, and η w − s Case ''c'' has the highest HTII index ( N H ) and η w − s . Greater values of HTI index were obtained when flow enters from Rmin . Cases ''a'' and ''d ∼ e'' are nominated as the worst designs in terms of η W − S and MF, respectively.